What is Cohabitation? The Colombian Supreme Court’s Spatial Assumptions in Survivor’s Pension Cases - Rodríguez Morales, Andrés (2024)
In this article I use legal geography to analyze the way in which the jurisprudence of the Labor Cassation Chamber of the Colombian Supreme Court of Justice assumes spatial imaginaries on the evidentiary standard of cohabitation as a couple. The factual pattern chosen is the study of the possible recognition of the survivor’s pension for the partner of the deceased; therefore, I present two arguments. First, that the spatial assumptions on which the concept of cohabitation as a couple is built are contradictory. Secondly, that when it comes to the existence of sexual relations within the framework of the couple’s relationship, the Supreme Court uses the public/private binary, traditionally used to oppress women, to emancipate them.